162k views
2 votes
Which statement is correct?

Which statement is correct?-example-1

1 Answer

5 votes

Answer:


(2.06*10^(-2))( 1.88*10^(-1)) < (7.69*10^(-2))/(2.3*10^(-5))

Explanation:

Verify each statement

Part 1) we have


(2.06*10^(-2))( 1.88*10^(-1)) < (7.69*10^(-2))/(2.3*10^(-5))

Solve the left side


(2.06*10^(-2))( 1.88*10^(-1))=(2.06*1.88)*10^(-2-1)


(3.8728)*10^(-3)

Solve the right side


(7.69*10^(-2))/(2.3*10^(-5))=(7.69)/(2.3)*10^(-2+5)


3.3435*10^(3)

substitute in the inequality


(3.8728)*10^(-3) < 3.3435*10^(3)


0.0038728 < 3,343.5 -----> is true

therefore

The statement is correct

Part 2) we have


(2.06*10^(-2))( 1.88*10^(-1)) \geq (7.69*10^(-2))/(2.3*10^(-5))

Solve the left side


(2.06*10^(-2))( 1.88*10^(-1))=(2.06*1.88)*10^(-2-1)


(3.8728)*10^(-3)

Solve the right side


(7.69*10^(-2))/(2.3*10^(-5))=(7.69)/(2.3)*10^(-2+5)


3.3435*10^(3)

substitute in the inequality


(3.8728)*10^(-3) \geq 3.3435*10^(3)


0.0038728 \geq 3,343.5 -----> is not true

therefore

The statement is not correct

Part 3) we have


(2.06*10^(-2))( 1.88*10^(-1)) > (7.69*10^(-2))/(2.3*10^(-5))

Solve the left side


(2.06*10^(-2))( 1.88*10^(-1))=(2.06*1.88)*10^(-2-1)


(3.8728)*10^(-3)

Solve the right side


(7.69*10^(-2))/(2.3*10^(-5))=(7.69)/(2.3)*10^(-2+5)


3.3435*10^(3)

substitute in the inequality


(3.8728)*10^(-3) > 3.3435*10^(3)


0.0038728 > 3,343.5 -----> is not true

therefore

The statement is not correct

Part 4) we have


(2.06*10^(-2))( 1.88*10^(-1)) = (7.69*10^(-2))/(2.3*10^(-5))

Solve the left side


(2.06*10^(-2))( 1.88*10^(-1))=(2.06*1.88)*10^(-2-1)


(3.8728)*10^(-3)

Solve the right side


(7.69*10^(-2))/(2.3*10^(-5))=(7.69)/(2.3)*10^(-2+5)


3.3435*10^(3)

substitute in the equation


(3.8728)*10^(-3) = 3.3435*10^(3)


0.0038728 = 3,343.5 -----> is not true

therefore

The statement is not correct

User Alex Riley
by
5.4k points